HOW IS THE JOURNEY OF STUDENT BUSINESS SUCCESS WITH ENTREPRENEURIAL PASSION AND FAMILY SUPPORT? Survey on Students Receiving Facilitation of Student Creative Business and Business (FUBKM) of Siliwangi University - Dila Fadlatul Hasanah; Edi Fitriana Afriza; Astri Srigustini (International Journal of Economics and Management Research, 2022)
The purpose of the study is to determine the influence of entrepreneurial passion and family support on entrepreneurial success. Explanatory survey is a research method that will be used in a population of 55 business groups with members of 191 students receiving Business Facilitation and Student Creative Business (FUBKM) of Siliwangi University. The purposive sampling technique used by considering the criteria that student efforts facilitated by Siliwangi University are still running, a total of 42 business groups consisting of 140 students. The results of the study explained that there is a significant influence both partial and simultaneous between entrepreneurial passion and family support on entrepreneurial success.